Розвиток архітектури садибного житла Львова кінця ХVІІІ – початку ХХІ століть - Якубовський, Ігор Вячеславович (Національний університет "Львівська політехніка", 2015)
У дисертації комплексно розглянуто проблему проектування садибного житла Львова протягом довгого хронологічного відтинку – майже 250 років (від кінця ХVІІІ до початку ХХІ століть). У роботі висвітлено суспільно-ідеологічний контекст розвитку архітектури садибного житла Львова, проаналізовано нормативні основи проектування та специфіку проектної діяльності. На основі архівної проектної документації виявлено особливості розвитку архітектури садибного житла міста в архітектурно-планувальному та стильовому аспектах, визначено її місце у світовому контексті. У дослідженні виявлено приклади реалізації передових європейських архітектурних концепцій у розвитку архітектури садибного житла в умовах Львова, а також встановлено значення історично сформованих архітектурно-планувальних та стильових вирішень для розвитку архітектури сучасного садибного житла. У дослідженні запропоновано напрями збереження наявного житлового фонду, а також можливі вектори розвитку сучасного садибного житла міста. В диссертации комплексно рассмотрена проблема проектирования усадебного жилья Львова в течение длинного хронологического отрезка – почти 250 лет (от конца ХVІІІ к началу ХХІ веков). В работе рассмотрено общественно- идеологический контекст развития архитектуры усадебного жилья Львова, проанализированы нормативные основы проектирования и специфика проектной деятельности. На основе архивной проектной документации определены особенности развития архитектуры усадебного жилья города в архитектурно-планировочном и стилевом аспектах, определенно ее место в мировом контексте. В исследовании представлены примеры реализации передовых европейских архитектурных концепций в развитии архитектуры усадебного жилья в условиях Львова, а также установлено значение исторически сформированных архітектурно-планировочных и стилевых решений для развития архитектуры современного усадебного жилья. В исследовании предложены направления сохранения существующего жилищного фонда, а также предложены возможные векторы развития современного усадебного жилья города. This thesis has complex review on the estate dwelling projecting problem in Lviv during long chronological period - almost 250 years (from the end of XVIII century till the beginning of XXI centuries). The research defines that the localization and development of estate dwelling architecture has been influenced by both external (ideological, social and economic situation) and internal issues (standards base development, organization structure of projecting activity, own architecture school development). It is defined that location of estate dwelling in Lviv took place in two directions: disperse object location and inside blocks of estate building. The main directions of city-building development of estate dwelling in Lviv are: concentrated building expanding from city center to the peripherals; building rotation (replacing estate dwelling areas with rapid multi-floor building); locating estate building areas with complexes; «moving» bounds of estate building zones; variety of city-building methods for ogranizing complexes of estate dwelling. This research develops typology of Lviv estate areas with following parameters: locating in building system, area square (large - 1 Ha and more, mid-size - from 0,4 till 1 Ha, small - less than 0,4 Ha), area configuration, relief type, house placement within the area, presence of additional buildings within the area, functional zone type and composition solution for general plan. The typology of estate houses in Lviv is developed with following parameters: volumespacial solution (standalone building, paired, blocked), amount of floors, amount of dwellings (one, two and four flats), general square of dwellings (minimal (up to 50 m²), small (50–200m²), mid-size (200–400 m²), large (400–1000 m²), extra large (more than 1000 m²); rooms type (minimal; optimal and extended); type of heating system (central, hallway, enfilade and combined). The main development directions are defined for architectural-planning solutions of estate dwelling. These consist of extending typology of estate dwelling, architectural-planning solutions, taking into account ideological, social and economic demands. The classification for researched period estate dwelling styling solutions is developed and shown that their evolution shows great variety and presence of all currently possible actual styling trends. And the style change dynamics refer to their connection with politic-ideological and social-economic context. The negative estate dwelling architecture development trends are defined which consist of losing building authencity and neglecting certain areas features; disharmony and disproportion of many modern renovations and additions; losing historical experience in projecting whole blocks of estate builing. The positive trends are the following: satisfying physical state of the builing, the possibility of agreement new builing with formed context with use of modern materials and technologies, reborn of local estate dwelling projecting traditions. The following saving of Lviv estate dwelling propositions are developed: definition of guarded zones and giving them the architecture monument status and local city-buiding (18 new objects proposed); definition of special rules for new building and reconstruction in historical estate dwelling areas (individual for each historical area); observance of demand for new object to be proper in the general architectural image of the area; identification of objects which cannot be changed in architectural image due to their special historical-architectural value.
Развитие архитектуры усадебного жилья Львова конца ХVІІІ – начала ХХІ веков
The estate dwelling architecture development in Lviv at the end of XVIII - beginning of XXI centureis
Keywords: садибне житло; архітектурно-планувальні вирішення; стильові вирішення; збереження та розвиток; усадебное жилье; архітектурно-планировочные решения; стилевые решения; сохранение и развитие; estate dwelling; architectural-planning solutions; styling solutions; saving and developing